MATHEMATICS TEACHERS’ ONLINE TEACHING EXPERIENCE IN TIMES OF SCHOOL CLOSURES: THE CASE OF MALAYSIA (Malaysian Journal of Learning and Instruction, 2022)
Purpose – Given that students were out of school in response to the COVID-19 pandemic public health measures, traditional teaching practices have been forced to switch to online mediated learning environments. This study represents the first research effort to capture the experience of Malaysian mathematics teachers about their teaching during the pandemic. This includes investigating digital education tools mathematics teachers used, issues they encountered, and the knowledge and skills they need to improve during the enforced online teaching situation.Methodology – This study employed a survey design and qualitative data were collected using an online questionnaire. A total of 202 primary and secondary mathematics teachers from Malaysia participated in the study. The data were analysed through thematic analysis and descriptive statistics.Findings – First, it was found that the mathematics teachers employed a variety of digital education tools during the pandemic and the most commonly used tool was WhatsApp. Second, the top two issues faced by the teacher respondents were due to internet problems and students’ engagement during the online learning. A particular striking finding revealed that three-fifths of the teacher respondents who were concerned about the issue of students’ engagement were secondary mathematics teachers. Third, findings of the study further clarified that most of the teacher respondents wanted to improve their technological skills.Significance – This study supports mathematics teachers in making informed decisions about their teaching during school closures. The findings of this study also serve to alert the education sector about the issues related to the implementation of online education in times of the pandemic. In general, this study necessitates in developing preparedness for future pandemics.